Fabricating a Polysulfone-ZIF-8 Composite Membrane for Separating CO2 and CH4 - Pouneh Ramezani; Omid Alizadeh; Masoud Mokhtary (Iranian Journal of Chemical Engineering)
In this research, a mixed matrix membrane based on polysulfone and zinc nitrate-methylimidazole fillers was synthesized to improve the ability of the polymer membrane for the separation of CO2 and CH4. The membranes were fabricated using the solution casting technique and characterized using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR-ATR), energy dispersive spectroscopy (EDAX), and gas permeability tests. The FTIR-ATR analysis confirmed the presence of the functional groups. XRD results demonstrated an even dispersion of the additives throughout the polymer matrix, by the quantitative analysis revealing a reduction in the crystal size and percentage. The EDAX analysis confirmed the consistent spread of ZIF-8 particles in the polymer. The gas permeability tests showed a significant increase in the permeability and selectivity of the mixed matrix membrane compared to that of the pure polysulfone membrane. The presence of ZIF-8 particles enhanced the permeability of CO2 by expanding the available space within the polymer and promoting the solubility of CO2. Additionally, the increased free volume improved the diffusion coefficient of CH4 and led to a slight increase in its permeability. The permeability of CO2 increased from 76.72 GPU for the pure polysulfone membrane to 322.95 GPU for the mixed matrix membrane, while the permeability of CH4 increased from 31.21 GPU to 61.27 GPU. The selectivity of CO2/CH4 exhibited a notable increase from 2.46 to 5.27. This improvement in selectivity can primarily be attributed to the significantly higher increase in the solubility coefficient of CO2 compared to that of CH4.